USING EFFECTIVE EXPOSURE TIME (EET) AS A MEASUREMENT OF EFL STUDENTS’ LEARNING - Chen, Ruhong (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Globalization promotes huge amount of English as a Foreign Language (EFL) learners. Effective and efficient measurements of English literacy become more and more necessary. Traditional assessments are usually carried out in the form of formal assessments which are prolonged, cost inefficient and unnecessary for most of the learners. It is important to identify an efficient and effective measurement of English literacy for EFL learners who do not live in an English environment and/or whose second language is not English. In this paper, through literature review and analysis on the existing learning assessment on EFL, ‘Effective Exposure Time’ (EET) is proposed as a measurement of EFL students’ learning from the social learning aspect. The EET is defined under the social learning theory as the exposure time in the formal and informal learning environments on learning comprehension (reading and listening) and production (writing and speaking) of EFL from the more knowledgeable others (teachers and non-teachers) in the Zone of Proximal Development (ZPD). By using the EET, EFL learning can be assessed efficiently and effectively.